PPDM Design for Optimizing the Potential Development of The Children’s Character Deserving in Menayu Village, Muntilan Sub District, Magelang - yanti, rohma; rohmayanti, rohmayanti (Muhammadiyah University Press, 2020)
Menayu Village is a village in Muntilan Sub district, Magelang which has been designated and established as the Children - Friendly Village. There are 6 indicators in the form of clusters in order to create the children – friendly village, namely; the realization of institutional strengthening clusters. The purpose of this activity is to form an organization that supports and strengthens the realization of the children - friendly village through various approaches to the community. The method to be used in achieving these goals is a participatory community empowerment (PRA) model. This method was chosen based on the consideration that the one who has or faces a problem is a partner, therefore the involvement of partners in determining the solution to the problem at hand and its solution is very much needed. Its activities include identification of problems, identification of resources owned, delivery of identification results, alternative solutions and problem solving as well as monitoring evaluation. The results obtained from this activity are the formation of The children - friendly village task force in Menayu Village, the involvement of the community and religious leaders in the institution of the Children - Friendly Village, the preparation of the Children - Friendly Village action plan, the formation of a Youth Information Center, Counseling and Youth Family Development. Conclusion: the effort to realize the children - friendly village must begin with institutional strengthening to ensure the sustainability of the children - friendly village program.